(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This research aims to determine the impact of risk disclosure on financial performance, specifically focusing on conventional banks listed in the Kuwait Stock Exchange, during the period from 2010 to 2024. The research sample consisted of five conventional banks listed on the Kuwait Stock Exchange: National Bank of Kuwait, Commercial Bank of Kuwait, Gulf Bank, Al-Ahli Bank of Kuwait, and Burgan Bank. The required data was obtained from the published annual reports of the banks under study. Data collection and analysis were conducted using E-Views-13 software. The research examined financial performance as a dependent variable, measured by return on equity (ROE) and return on assets (ROA), and risk disclosure as an independent variable, measured using content analysis of the annual report. Risk disclosure was calculated as the ratio of the number of items in the index used to the total number of index items. Control variables were also measured: financial leverage, calculated as the ratio of total assets to total liabilities, and bank size, calculated as the natural logarithm of the bank’s total assets. The results showed: No impact of risk disclosure on financial performance, as measured by ROE and ROA for banks listed on the Kuwait Stock Exchange